SARS-CoV-2 COVID-19 infection in children and adolescents: epidemiological, clinical and evolutionary characteristics in a pediatric population: Police Hospital, March 13, 2020 to April 30, 2021 (Archives of Pediatrics of Uruguay, 2022)
Introduction: the World Health Organization declared the SARS-CoV-2 COVID-19 pandemic on 3/11/2020. In Uruguay on 3/13/2020 the first cases were reported, and a state of health emergency was declared. From the beginning of the epidemic until 04/27/2021 there were 22,718 cases in the pediatric population of the country. This epidemiological situation at the Department of Pediatrics led to the diagnosis and clinical follow-up of all children and adolescents (NNA) treated at the Police Hospital, suspicious or confirmed cases and/or COVID-19 contacts through telephone check-up appointments.Objective: describe the epidemiological, clinical and evolutionary characteristics of children and adolescent users of the Police Hospital diagnosed with SARS-CoV-2 COVID-19 infection between 3/13/2020 and 4/30/2021.Methodology: a retrospective descriptive observational study was carried out from 3/13/2020 to 4/30/2021. All children from 0 to 14 years old with an identified diagnosis of SARS-CoV-2 COVID-19 infection were required a follow-up at the Department of Pediatrics of the Police Hospital. A case of infection by SARS-CoV-2 was that of any child or adolescent with a positive PCR test result or epidemiological link.Data source: medical and laboratory records. The following variables were considered: sex, age, origin, clinical manifestations, place of care (home or hospital), test for SARS-CoV-2, evolution. Statistical analysis was established based on the frequency distribution and summary measures.Results: 260 children had COVID-19 in the period analyzed. 65% presented symptoms, 33% were asymptomatic and in 2% no data were found. Regarding age, 4.6% were infants, 10.8% preschoolers, 36.2% schoolchildren, and 48.4% adolescents. The frequency distribution of cases according to the month was 1.2% positive cases in October, 0.8% in November, 5.4% in December, 13.5% in January, 7% in February, 30% in March and 42.1% in April.Conclusions: the children and adolescents with SARS-CoV-2 COVID-19 infection were a low percentage of the pediatric population of the Police Hospital in the period analyzed. However, in this period it grew exponentially, which goes in line with the evolution of the epidemic in the country. Although 65% had a symptomatic disease, almost all were mild cases and were treated on an outpatient basis. A single patient required hospitalization. None died.
Keywords: SARS-CoV-2; Child; Adolescent; COVID-19